Effect of angiotensin-converting enzyme gene polymorphism at the results of losartan use in the patients with type 2 diabetes mellitus - T. Yu. Poniatowskaya (Kazimierz Wielki University, 2015)
Poniatowskaya T. Yu. Effect of angiotensin-converting enzyme gene polymorphism at the results of losartan use in the patients with type 2 diabetes mellitus. Journal of Education, Health and Sport. 2015;5(3):55-61. ISSN 2391-8306. DOI: 10.5281/zenodo.16210 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A55-61 https://pbn.nauka.gov.pl/works/547306 http://dx.doi.org/10.5281/zenodo.16210 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   EFFECT OF ANGIOTENSIN-CONVERTING ENZYME GENE POLYMORPHISM AT THE RESULTS OF LOSARTAN USE IN THE PATIENTS WITH TYPE 2 DIABETES MELLITUS   T. Yu. Poniatowskaya   Odessa National Medical University   Summary The article presented is an original investigation where the effects of losartan in patients with hypertension and type 2 diabetes mellitus (T2DM) have been evaluated. The effect of therapy has been estimated with the help of gene ACE allelic variant. The dependence of enalapril antihypertensive action and nephroprotective action of ACE polymorphism has been revealed. The results obtained show a different effect on ACE allele variants of lipid metabolism in patients with hypertension and T2DM and complications in the form of hypertriglyceridemia in the patients with DD-genotype.   Key words: type 2 diabetes mellitus, hypertension, I / D polymorphism of the gene ACE, pharmacogenetics, losartan.